Proteomic Analysis of Copper Toxicity in Human Fungal Pathogen Cryptococcus neoformans - Sun, Tianshu; Li, Yanjian; Li, Yingxing; Li, Hailong; Gong, Yiyi; Wu, Jianqiang; Ning, Yating; Ding, Chen; Xu, Yingchun (Frontiers in Cellular and Infection Microbiology, 2021)
Cryptococcus neoformans is an invasive human fungal pathogen that causes more than 181,000 deaths each year. Studies have demonstrated that pulmonary C. neoformans infection induces innate immune responses involving copper, and copper detoxification in C. neoformans improves its fitness and pathogenicity during pulmonary C. neoformans infection. However, the molecular mechanism by which copper inhibits C. neoformans proliferation is unclear. We used a metallothionein double-knockout C. neoformans mutant that was highly sensitive to copper to demonstrate that exogenous copper ions inhibit fungal cell growth by inducing reactive oxygen species generation. Using liquid chromatography-tandem mass spectrometry, we found that copper down-regulated factors involved in protein translation, but up-regulated proteins involved in ubiquitin-mediated protein degradation. We propose that the down-regulation of protein synthesis and the up-regulation of protein degradation are the main effects of copper toxicity. The ubiquitin modification of total protein and proteasome activity were promoted under copper stress, and inhibition of the proteasome pathway alleviated copper toxicity. Our proteomic analysis sheds new light on the antifungal mechanisms of copper.